The influence of selected treatment parameters with atmospheric plasma on the treatment process and wood wettability - Žigon, Jure (Les (Ljubljana), 2020)
The paper presents the use of low-temperature plasma, generated in the air at atmospheric pressure, for treatment of wood surfaces to improve their wettability. For this purpose, a dielectric barrier discharge plasma device with a floating electrode configuration was used. The density and homogeneity of the plasma discharge, formed between the isolated high voltage electrodes and the surface of the spruce (Picea abies (L.) Karst.) and beech (Fagus sylvatica L.) wood, was shown to be highly dependent on the size of the gap between the electrode and wood. Topography measurements using a confocal laser microscope showed that exposure of wood to plasma causes changes on its surface at the sub-microscopic level. Measurements of the contact angles of water droplets and water-based coating showed the improved susceptibility to wetting of treated surfaces. Differences in surface wettability were also detected depending on the selected treatment parameters: type of wood, workpiece feed speed, the distance between the electrodes, the distance between the electrodes and workpiece, and workpiece thickness.
Keywords: contact angle; les; omočljivost; plasma; plazma; stični kot; voda; water; wettability; wood